Comparação entre a máxima velocidade aeróbia e seu respectivo tempo limite determinado por diferentes métodos e sua relação com a performance de corredores - Silva, Danilo Fernandes da (2012)
Maximal aerobic speed (MAS) and its respective time limit (tlim) are predictors of aerobic performance in runners. Velocity associated with the occurence of maximal oxygen uptake (vVO2max) and peak running speed (Vpeak) are two variables related to MAS and are determined by different methods. The Vpeak, in special, seems to be of great pratical relevance because it can be determined without a metabolic cart necessary to the determination of vVO2max. However, few studies determined it, especially with its tlim. The objective of the present study was to determine MAS and its tlim using two different methods. Participants were twenty one runners aged 41.2 ± 6.9 years, body mass of 75.4 ± 11.4 kg, height of 173.9 ± 7.8 cm, body mass índex of 24.8 ± 2.4 kg.m-2, maximal oxygen uptake (VO2max) of 54.0 ± 7.6 mL.kg-1.min-1 and experience in competing between 5 and 15 km (practice time of 10.9 ± 11.1 years). Participants were submitted, randomly, to two incremental continuous tests of maximal effort in laboratory (automatic ergometric treadmill with multiprogram, INBRAMED Super ATL, Porto Alegre - Brazil), with treadmill grade set at 1%, to determine vVO2max and Vpeak. vVO2max was determined with the equation proposed by Lacour et al. (1990, 1991) based on energetc cost of running (CR), on VO2max and on rest oxygen uptake (VO2rest), the last two variables determined by an espirometry open system Fitmate (COSMED®, Rome - Italy). Vpeak was determined by a "clean" incremental protocol, which means, without the espirometry, being considered the higher velocity attained during the test. The incremental test was preceed by a warm up of three minutes at 7 km.h-1 and initiated at 9 km.h-1 with increments of 1 km.h-1 each three minutes. The tests were maintened until volational exhaustion and participants were encouraged verbally to keep as long as possible in effort. After each incremental test, it was conducted, randomly, two tests to determine tlim at 100% of vVO2max and Vpeak. Besides laboratorial tests, participants did two performances, one of 10 and the other of 15 km, conducted in a field track of 400 meters. Data was presented at mean ± standard deviation. It was used the Shapiro-Wilk test to verify the normality of data distribution, t test to related samples to compare methods, concordance test of Bland-Altman (1986) and Pearson coefficient of correlation; adopting significance level of p<0.05. The results showed that vVO2max (15.5 ± 1.7 km.h-1) was significantly higher than Vpeak (15.2 ± 1.4 km.h-1). It was also observed statisticaly significant difference between tlim at vVO2max (5.4 ± 2.1 min) and tlim at Vpeak (6.3 ± 1.4 min). Correlations between Vpeak and performances were more elevated (10 km r = 0.77; 15 km r = 0.75) than correlations between vVO2max and the same performances (10 km r = 0.65; 15 km r = 0.64). Besides, tlim at Vpeak presented relation with 10 (r = -0.44) and 15 km (r = -0.45), relation that was not observed between tlim at vVO2max and performances. In conclusion, Vpeak presented correlations more elevated iii iv with performances of 10 and 15 km than vVO2max. The tlim in Vpeak also presented correlation statistically significant with performances, relation that was not observed between tlim in vVO2max and performances.